Targeting melanocortin receptor type 1 with small peptides. (1st July 2019) - Slominski, A.T.; Slominski, R.M.; Zmijewski, M.A.
Abstract : Linked Article : Kim et al. Br J Dermatol 2019; 181 :128–137 .